Euphorbia pallens Dillw., the correct name for Euphorbia articulata Dennst., the sea-shore species from India - Raju, Vatsavaya S. (Rheedea, 2001)
The name Euphorbia articulata Dennst., as applied to the species occurring in the Malabar coast of Peninsular India, but distinct from E. atoto Forst. f. is a later homonym and illegitimate. When E. halophila Miquel is treated as conspecific to E. articulata Dennst., the correct name of the species is E. pallens Dillw.